DEFECT PRODUCT REDUCTION IN RICE PRODUCTION AT UD JAVA DWIPA USING SIX SIGMA METHOD - Reza Ahaddin Ramadhan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The organic rice production process at UD Java Dwipa has faced recurring quality defects, including loosened packaging, contamination with unwanted materials, expired products, and dirty packaging. These issues have led to increased operational costs, inefficiencies, and declining customer satisfaction, raising concerns about the company's ability to consistently deliver high-quality organic rice to its customers. Given the growing competition in the organic rice market and the importance of maintaining product integrity, addressing these challenges is critical for UD Java Dwipa to sustain its market position and reputation. This research employs the Six Sigma DMAIC framework to systematically identify, analyze, and mitigate the root causes of defects. Data collection methods include Failure Mode and Effects Analysis (FMEA), Pareto analysis, and fishbone diagrams, complemented by insights from interviews and production data reviews. Key corrective actions prioritized based on frequency and impact include developing stricter Standard Operating Procedures (SOPs), providing comprehensive operator training, and implementing preventive maintenance for sealing machines. A control phase ensures sustainability through regular audits, real-time defect monitoring, and enhanced process documentation. The findings demonstrate significant reductions in defect rates and improvements in operational efficiency following the implementation of corrective measures. The process capability improved, with the Sigma Level increasing from 3.69 to 4.06, reflecting enhanced production consistency. These results highlight the effectiveness of a structured quality management approach in resolving production challenges and emphasize the importance of continuous monitoring to maintain quality standards in the competitive organic rice market.